Use of Social Networking Sites among University Students in Ajman, United Arab Emirates - Karuppasamy, G; Anwar, A; Bhartiya, A; Sajjad, S; Rashid, M; Mathew, E; Saikh, R B; Sharbatti, S Al; Sreedharan, Jayadevan (Nepal Journal of Epidemiology, 2013)
Note: a new paragraph 'What this study adds:' was added to page 250 on 27 March 2014. Background Social networking sites are web-based services through which individuals can create a public or semi-public profile within a bounded system, connect with a list of other linked users, and view and interact with a list of their connections and with those made by others within the system. To estimate the proportion of university students using social networking sites (SNS) and to determine the association between SNS use and age, gender, nationality, course and year of study, living context, family size, number of close friends, close relationships, stress related to studies and interpersonal relationships. Materials and Methods A cross sectional study was carried out among 300 students from two universities in Ajman, UAE. A self-administered, content-validated and pilot-tested questionnaire was used. The participants answered questions related to their use of social networking sites and details of socio-demographic variables. The data collected were entered into Microsoft Excel and transferred to PASW 18.0 version. Data were analyzed as frequencies, percentages, means and SDs, and Chi-square test used for associations. The odd ratio was calculated for the significant variables to find the degree of association. The SNS usage was categorized as average, moderate or high based on mean and SD on the SNS test score. Results The study population was comprised of 41.6% males and 58.3% females. 89% used social networking sites (SNS) and 11% were non-users. Of the 267 users of SNS, 58.8% were average users, 37.8% moderate users and 3.4% high users. Students in the first and second years of study, small family size, age below 20 years, male gender, being in a non-medical study program, friends in close relationship were found to be associated with higher SNS use. Conclusion Social networking sites were found to be popular among a large number of university students in the UAE, this being more so among males and non-medical students of first two years of study. DOI: http://doi.dx.org/10.3126/nje.v3i2.8512